Effects of restricted vs. step up dietary adaptation for 6 or 9 days on feedlot performance, feeding behaviour, ruminal and blood variables of Nellore cattle - Perdigão, A. [UNESP]; Millen, D. D. [UNESP]; Brichi, A. L.C. [UNESP]; Vicari, D. V.F. [UNESP]; Franzói, M. C.S. [UNESP]; Barducci, R. S. [UNESP]; Martins, C. L. [UNESP]; Estevam, D. D. [UNESP]; Cesar, M. T. [UNESP]; Arrigoni, M. D.B. [UNESP] (Wiley, 2018)
This study was designed to determine effects of quantitatively restricted intake of the final finishing diet as a means of dietary adaptation compared with diets increasing in concentrate (step up) over periods of 6 and 9 days on feedlot performance, carcass characteristics, feeding behaviour, blood gas profile and rumen morphometrics of Nellore cattle. One hundred twenty 22-month-old Nellore bulls (352 ± 20 kg) were randomly allocated in 24 pens and fed for 84 days. The experimental design was a completely randomized block with 2 × 2 factorial arrangement of treatments: adaptation using either step up protocol for 6 days or 9 days or restriction protocol for 6 days or 9 days, where the pen (five bullocks/pen; six pens/treatment) was considered the experimental unit. Cattle adapted by step up protocol had significantly greater average daily gain throughout the study when compared to those adapted by restriction protocol, regardless of adaptation length. During the adaptation period, a greater dry matter intake fluctuation was observed for animals maintained on restriction programme when compared to those adapted to the finishing diets using step up protocol. In addition, a protocol × length interaction for rumenitis scores was observed, where the level of injuries to the ruminal wall was significantly higher for the cattle adapted by restriction protocol for 9 days and lower for animals submitted for 9 days to the step up programme. Likewise, a protocol × length interaction for mitotic index was observed, in which cattle adapted by step up protocol for 9 days had lower numbers of cells in mitosis. Thus, the step up protocol led to better feedlot performance, and based on this fact, the length of 9 days promoted better rumen epithelium adaptation of Nellore cattle to high-concentrate diets.
Keywords: concentrate; intake; papillae; protocol; rumen